1998
DOI: 10.1164/ajrccm.158.4.9802091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Methods Used to Evaluate Dyspnea in Patients with Chronic Obstructive Pulmonary Disease

Abstract: When dyspnea must be assessed clinically, there are three methods of assessment: the measurement of dyspnea with activities of daily living using clinical dyspnea ratings such as the modified Medical Research Council (MRC), the Baseline Dyspnea Index (BDI), and the Oxygen Cost Diagram (OCD); the measurement of dyspnea during exercise using the Borg scale; to assess the influence of dyspnea on health-related quality of life (HRQoL) using disease-specific questionnaires such as the St. George's Respiratory Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
1
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(198 citation statements)
references
References 16 publications
8
176
1
13
Order By: Relevance
“…Patients hospitalized for CAP presented lower performance on the 6MWT (66% of predicted), indicating a reduction in FC, as previously demonstrated in patients with stable COPD [22][23][24] . In a study by Solh et al 7 , elderly patients hospitalized for CAP showed a decline in functional capacity as assessed by an ADL scale.…”
Section: Discussionsupporting
confidence: 75%
“…Patients hospitalized for CAP presented lower performance on the 6MWT (66% of predicted), indicating a reduction in FC, as previously demonstrated in patients with stable COPD [22][23][24] . In a study by Solh et al 7 , elderly patients hospitalized for CAP showed a decline in functional capacity as assessed by an ADL scale.…”
Section: Discussionsupporting
confidence: 75%
“…Clinical characteristics collected included age, sex, body mass index (BMI), and subjective dyspnea as measured by the Modified Medical Research Council (MMRC) dyspnea scale. 19 Approval was obtained from the Mayo Foundation Institutional Review Board.…”
Section: Subjectsmentioning
confidence: 99%
“…Bij 27 deelnemers (6%) was de spirometrietest niet adequaat en bij 14 deelnemers (3%) waren een of meer vragenlijsten 23 De meeste rokers zonder eerdere diagnose COPD hebben een lichte vorm van de aandoening. Onze resultaten zijn daarom niet zonder meer van toepassing op patiënten met ernstig COPD.…”
Section: Resultaatunclassified